International Instruments of Protection of Right of Union Association (2017)
This work is eminently legal-normative and is developed with a documentary methodology, in which it is intended to build a tool that allows a clear understanding of the applicable international instruments in Colombia to guarantee the human right of trade union association. In this sense, it analyzes the guarantees of the human right of trade union association, enshrined in international instruments, based on the study of the universal and American system, in order to identify the applicable prerogatives in the Colombian legal system.